2009
DOI: 10.3945/ajcn.2009.27462n
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual variation in umami taste and polymorphisms in TAS1R taste receptor genes

Abstract: There is a reliable and valid variation in human umami taste of l-glutamate. Variations in perception of umami taste correlated with variations in the human TAS1R3 gene. The putative human taste receptor TAS1R1-TAS1R3 responds specifically to l-glutamate mixed with the ribonucleotide IMP. Thus, this receptor likely contributes to human umami taste perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
4
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 76 publications
4
86
4
5
Order By: Relevance
“…Some people are specifically insensitive to MSG, 97 which is partly caused by alleles of the umami receptor. 98-100 The detection of a genotype/phenotype relationship implies that the trait is at least partially heritable, but we know of no published twin or family studies that estimate the contribution of genes to trait variation.…”
Section: Umami: Savory or Meatymentioning
confidence: 99%
See 1 more Smart Citation
“…Some people are specifically insensitive to MSG, 97 which is partly caused by alleles of the umami receptor. 98-100 The detection of a genotype/phenotype relationship implies that the trait is at least partially heritable, but we know of no published twin or family studies that estimate the contribution of genes to trait variation.…”
Section: Umami: Savory or Meatymentioning
confidence: 99%
“…Taking a ham and cheese sandwich as an example (Fig. 1), we might imagine that people with sensitive alleles might differentially detect the mild sweetness of onion (TAS1R3), 89 the savory glutamate taste of tomato (TAS1R3), 98,100,170 the bitterness of watercress (TAS2R38), 50 the smell of cheese (OR11H7), 154 or the boar taint odor of ham (OR7D4). 153 We envision that a combination of allelic differences might contribute to the range of liking for this sandwich.…”
Section: Taste Genetics and Food Intakementioning
confidence: 99%
“…The taste word 'umami' connotes the quality best exemplified by monosodium glutamate. Some people cannot taste umami [65,66], perhaps due in part to genetic variants within its receptor, TAS1R1 (taste receptor type 1 member 1), a heterodimer composed of T1R1 and T1R3, two proteins of the TAS1R family (Table 1) [18,[67][68][69][70][71]. In addition to this receptor, glutamate may also be sensed by receptors similar to those that recognize glutamate in the brain [72].…”
Section: Differences In Umami Sour and Salty Taste Detectionmentioning
confidence: 99%
“…Two additional SNPs, C329T in TAS1R1 and C2269T in TAS1R3, have been identified in nontasters, and G1114A in TAS1R1 has been identified in tasters. 121 Chen et al 122 demonstrated that variations in perception of umami taste correlate with R757C, A5T, and R247H in the human TAS1R3 gene. While many different genotypes have been elucidated, genetic variation alone cannot necessarily explain alterations in umami food intake.…”
Section: Genetic Chemosensory Variationmentioning
confidence: 99%